Rates and Predictors of Invalid Baseline Test Performance in High School and Collegiate Athletes for 3 Computerized Neurocognitive Tests: ANAM, Axon Sports, and ImPACT. (August 2015) - Nelson, Lindsay D.; Pfaller, Adam Y.; Rein, Lisa E.; McCrea, Michael A.
Background: Preseason baseline testing using computerized neurocognitive tests (CNTs) is increasingly performed on athletes. Adequate effort is critical to establish valid estimates of ability, but many users do not evaluate performance validity, and the conditions that affect validity are not well understood across the available CNTs. Purpose: To examine the rates and predictors of invalid baseline performance for 3 popular CNTs: Automated Neuropsychological Assessment Metrics (ANAM), Axon Sports, and Immediate Post-Concussion and Cognitive Testing (ImPACT). Study Design: Controlled laboratory study. Methods: High school and collegiate athletes (N = 2063) completed 2 of 3 CNTs each during preseason evaluations. All possible pairings were present across the sample, and the order of administration was randomized. Examiners provided 1-on-1, scripted pretest instructions, emphasizing the importance of good effort. Profile validity was determined by the manufacturers' standard criteria. Results: The overall percentage of tests flagged as of questionable validity was lowest for ImPACT (2.7%) and higher for ANAM and Axon (10.7% and 11.3%, respectively). The majority of invalid baseline profiles were flagged as such because of failure on only 1 validity criterion. Several athlete and testing factors (eg, attention deficit hyperactivity disorder [ADHD], estimated general intellectual ability, administration order) predicted validity status for 1 or more CNTs. Considering only first CNT administrations and participants without ADHD and/or a learning disability (n = 1835) brought the rates of invalid baseline performances to 2.1%, 8.8%, and 7.0% for ImPACT, ANAM, and Axon, respectively. Invalid profiles on the Medical Symptom Validity Test (MSVT) were rare (1.8% of participants) and demonstrated poor correspondence to CNT validity outcomes. Conclusion: The validity criteria for these CNTs may not identify the same causes of invalidity or be equally sensitive to effort. The validity indicators may not be equally appropriate for some athletes (eg, those with neurodevelopmental disorders). Clinical Relevance: The data suggest that athletes do not put forth widespread low effort or that some validity criteria are more sensitive to invalid performance than others. It is important for examiners to be aware of the conditions that maximize the quality of baseline assessments and to understand what sources of invalid performance are captured by the validity criteria that they obtain.